Kontribusi Regulasi Emosi terhadap Kecemasan pada Ibu Hamil di Kehamilan Pertama - Mayenrisari Arifin A. Pasinringi; Aulia Salsabila Burhanuddin; Fidya Ainun Cholisa; Nur Inayah Musa; Elfydha Siti Safrina (Jurnal Health Sains, 2021)
Anxiety can occur in pregnant women in the first pregnancy, one of which is because they have difficulty to regulate proper emotions. The negative impact of anxiety triggers uterine contractions, increased blood pressure, preeclampsia and even miscarriage. When the experience and expression of emotions can be managed properly then it can have an impact on the lack of anxiety symptoms that appear and of course improve the psychological well-being of pregnant women. This study aims to find out the contribution of emotional regulation to anxiety in pregnant women in the first pregnancy. A study sample of 34 people with an age range of 20-37 years using purposive sampling techniques. The measurement tools used are Emotion Regulation Questionnaire (ERQ) and Zung Self-rating Anxiety. The data is analyzed using a simple regression test. The results showed that emotion regulation contributed significantly to anxiety in pregnant women in the first pregnancy with a correlation index value (R) of 40.2%. Emotion regulation contributed to anxiety (R2) by 16.2% and 83.8% was affected by other variables outside the study